Prevalence and pattern of birth defects in a tertiary health facility in the Niger Delta area of Nigeria - Abbey M; Oloyede OA; Bassey G; Kejeh BM; Otaigbe BE; Opara PI; Eneh AU; Akani CI (Dove Medical Press, 2017)
Mkpe Abbey,1 Olufemi A Oloyede,2 Goddy Bassey,1 Benjamin M Kejeh,3 Barbara E Otaigbe,4 Peace I Opara,4 Austa U Eneh,4 Chris I Akani1 1Department of Obstetrics and Gynaecology, University of Port Harcourt Teaching Hospital, Port Harcourt, 2Department of Obstetrics and Gynaecology, Olabisi Onabanjo University Teaching Hospital, Sagamu, 3Department of Surgery, 4Department of Paediatrics, University of Port Harcourt Teaching Hospital, Port Harcourt, Nigeria Objective: To ascertain the prevalence and pattern of congenital abnormalities that are peculiar to the Niger Delta area of Nigeria. Methods: This is a descriptive retrospective cross-sectional study. It involved data from the labor ward and neonatal birth registers of the University of Port Harcourt Teaching Hospital on the total number of births and the babies that were delivered with major birth defects between August 2011 and December 2014. We also conducted a statistical comparison of the prevalence of congenital abnormalities in the Niger Delta with that in other regions of Nigeria and the developed world of Europe. Results: Out of the 7,670 deliveries that occurred, 159 maternities had babies with major birth defects giving a prevalence of 20.73 cases per 1,000 live births. This figure is far more than that which was obtained in other regions of Nigeria –4.15:cases per 1,000 live births in the South East (P<0.001), 15.84:1,000 in the South West (P<0.01), and 5.51:1,000 in the North East (P<0.001). Eighty-five (53.46%) of the defects occurred in 1,681 unbooked patients, while 74 (46.54%) happened in 5,989 booked maternities (P<0.001). The predominant abnormalities were those of the central nervous system at 27.0%, gastrointestinal system 11.95%, cardiovascular system 10.69%, anterior abdominal wall 8.18%, skeleton 6.29%, and chromosomal abnormalities at 5.66%. Conclusion: The prevalence of major birth defects at the University of Port Harcourt Teaching Hospital was 20.73 cases per 1,000 live births and it was more in the unbooked than the booked maternities. All body systems were affected with those of the central nervous system predominating at 27.0% of the total diagnosed defects. Keywords: maternity, congenital abnormalities, birth defects, unbooked, booked, Niger Delta, Port Harcourt